Plug it, fill it and forget it! - R Arpitha; Rajesh Ramanjulu; Mahesh P Shanmugam (Indian Journal of Ophthalmology, 2022)
Background: Management of posterior scleral perforation is commonly done with cryotherapy/laser or scleral patch graft depending on the size of perforation. However, for large perforations, the availability of donor sclera is always an issue. To overcome this problem, we tried using absorbable gelatin sponge to plug the perforation as an alternative. Purpose: To evaluate the efficacy of gelatin foam as an alternative to scleral patch graft in cases with perforation of posterior sclera. Synopsis: Here we report the case of a 27-year-old male, who sustained penetrating injury to right eye with two metallic intraocular foreign bodies with visual acuity of hand movement close to face. Primary wound repair was done, followed by retrieval of the first piece of metallic foreign body that measured 11X3mm in size. The second foreign body visualized at posterior pole adjascent to the disc was removed using Machemar forceps and it measured 10X3 mmin size. Leakage of PFCL at the site confirmed a posterior scleral perforation. Cryotherapy was avoided due to its proximity to optic nerve head, and donor sclera was not readily available at that moment. We managed the case by plugging the defect with absorbable gelatin foam, followed by silicone oil injection into the vitreous cavity. Post operative outcome was good with restoration of anatomical integrity of the globe along with improvement in visual acuity upto 6/18. Highlights: Gelatin foam being absorbable and inciting less reaction aids in sealing the perforation and maintenance of globe contour with the advantage being readily available, cost-effective and it can be left in situ without the need for additional surgery for its removal. This would be of use in situations where the donor sclera is not readily available, and thus can be a potential alternative. However, further studies with larger sample size need to be done to evaluate and compare its effectiveness over donor scleral grafts. Online Video Link: https://youtu.be/fkardnkMQQo